Remediation of pesticides using TiO2 based photocatalytic strategies: A review. (August 2022) - Zeshan, Muhammad; Bhatti, Ijaz A.; Mohsin, Muhammad; Iqbal, Munawar; Amjed, Nyla; Nisar, Jan; AlMasoud, Najla; Alomar, Taghrid S.
Abstract: Nowadays, pesticides are regarded as the most dangerous of the various organic pollutants, posing substantial environmental and human threats worldwide. Pesticide contamination has become one of the most crucial environmental issues due to its bio-persistence and bioaccumulation. Different conventional methods are being utilized for pesticide removal, yet pesticides are thought to be significantly present in the environment. The development and application of sophisticated wastewater treatment methods are being pursued to remove contaminants effectively, particularly pesticides. In the past several decades, nanoscience and nanotechnology have emerged as essential tools for the identification, removal, and mineralization of persistent pesticides by employing advanced nanomaterials such as pristine titanium dioxide (TiO2 ), doped TiO2, nanocomposites (NCs) TiO2, and ternary nanocomposites (TNCs) TiO2 by advanced oxidation processes (AOPs). Advancement in the characteristics of TiO2 by doping, co-doping, construction of NCs and TNCs has contributed to the dramatic efficiency up-gradation by reducing band gap, solar active photocatalyst, enhancing PCA, high photostability, chemically inertness and multiple time reusability. Based on previous literature, utilizing La–TiO2 NCs photocatalyst, the mineralization of pesticide (imidacloprid) attained up to 98.17% that is almost 40–53% greater than pristine TiO2 . The present review attempt to discuss the recent research performed on TiO2 based nanoparticles (NPs) and NCs for photocatalytic mineralization of various pesticides. The basic mechanism of TiO2 photocatalysis, types of reactors used for photocatalysis, and optimized experimental conditions of TiO2 for pesticides mineralization are discussed. Graphical abstract: Image 1 Highlights: The TiO2 based NPs and NCS for photocatalytic mineralization of pesticides is reviewed. The mechanism and types of reactors used for photocatalysis has been discussed. Optimum conditions for pesticides mineralization have been evaluated. Modified TiO2 are active under visible light and economical for remediation of pesticides.